Patterns of substance use in people with severe mental illness: A case-control study in Ethiopia - Melkam Alemayehu; Awoke Mihretu; Ruth Tsigebrhan; Manasi Sharma; Bizu Gelaye; Solomon Teferra (PLoS ONE, 2025)
Background Substance use disorders are increasingly prevalent in sub-Saharan African countries, with evident bidirectional risk for people with severe mental illness (SMI) resulting in more severe and chronic courses. This study examines the association between common substance use, including khat and alcohol, and SMI, comparing affected individuals to age and sex-matched controls in Ethiopia. Method This study uses data collected as part of the NeuroGAP-Psychosis project, a large multi-country case-control genetics study. This case-control study consisted of 6,500 people with severe mental illness and age and sex-matched 6,500 controls in Ethiopia. Current substance use was defined as any use within the last three months, while current regular use was defined as at least weekly use within the previous three months. Descriptive statistics were used to determine the demographic distribution of participants, and logistic regression was used to estimate the association between substance use and severe mental illness. Results Most cases were men (65.8%; n = 4,276) with a mean age of 36.9 (SD = 10.3) years, while the controls were 64.7% (n = 4,204) men with a mean age of 36.2 (SD = 10.9) years. Current use of tobacco, alcohol, khat, and cannabis was 15.1%, 17.2%, 20.4% and 1.0% among cases and 6.0%, 41.5%, 12.5%, and 0.8% among controls, respectively. The adjusted odds of regular tobacco and khat use were 4.8 (95% CI: 4.0, 5.9) and 1.6 (95% CI: 1.4, 1.8) times higher in cases than in controls, respectively. However, regular use of alcohol was 0.1 (95% CI: 0.1, 0.2) times lower among cases than among controls. Conclusions Tobacco and khat use were higher among cases than controls, while alcohol and cannabis use were more prevalent in controls. The high prevalence of khat use is particularly problematic in people with SMI as it adversely affects the course and outcome of mental illness. Tobacco smoking also contributes to physical health morbidity and associated premature mortality. Therefore, evidence-based screening and treatment services are warranted to mitigate the harmful health outcomes of khat use and tobacco consumption among individuals with SMI.